Effectiveness of the Use of AFO Rigid in Cases of Postoperative Diabetes Mellitus Charcot Joint - Nur Rachmat; Zenitha Bela Pratiwi Kusumawati (Pusat Unggulan IPTEK POLTEKKES KEMENKES Malang, 2022)
Charcot feet are a condition that affects the bones, joints, and soft tissues of the feet and ankles, where the initial phase is characterized by inflammation. Charcot states that joint damage is related to central nervous system damage that controls joint and bone nutrition. Repeated trauma to the denervation joint is a factor that accelerates the onset of CN. This study uses qualitative research, and the results of this study are descriptive. The results of interviews with patients. The patient cannot stand to rest on the foot. The purpose of the orthosis is for fixation. Before using a rigid AFO the patient performs his activities by way of peeling to the floor. With the use of rigid AFO this can help patients in their daily activities more independently, so as to improve the quality of life of patients.